Modul Pembuatan Blazer Sebagai Media Pembelajaran Pada Mata Pelajaran Costume Mode Kelas XII Tata Busana SMK N 3 Payakumbuh - Mardalena, Tari Novelia; Nelmira, Weni (Universitas Batanghari Jambi, 2024)
This research was motivated by the fact that class This research aims to develop a valid and practical Blazer Making Module, so that the resulting module can be used by students as a learning resource and guide in Blazer Making learning activities. This research uses the Research and Development (R&D) method with 4-D (Four D) development procedures. The type of data in this research is primary data obtained directly through validity testing and practicality testing. The validity test was carried out by 1 media expert validator and 2 material expert validators, while the practicality test was carried out by subject teachers, 43 class XII students for small- scale and large-scale trial research. Data collection techniques through interviews, observation and questionnaires. The data analysis technique uses descriptive analysis techniques using average scores and percentages in the form of assessments on a Likert scale. Based on research data, the Blazer Making media module is categorized as very suitable as a learning media by having validation test results from media experts and material experts with a score of 83.9% in the very valid category, while the practicality test with subject teachers obtained a score of 95.3% in the very practical category, then the results of the small scale trial got a score of 93.1% in the very practical category, and the results of the large scale trial got a score of 95.2% in the very practical category. The results above show that the Blazer Making media module is very valid and practical as a learning resource and guide in the teaching and learning process.